2020
DOI: 10.1002/adma.202000496
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Polarization in Inverse Spinel‐Structured Mg2TiO4 Coating to Suppress Oxygen Evolution of Li‐Rich Cathode Materials

Abstract: High‐energy Li‐rich layered cathode materials (≈900 Wh kg−1) suffer from severe capacity and voltage decay during cycling, which is associated with layered‐to‐spinel phase transition and oxygen redox reaction. Current efforts mainly focus on surface modification to suppress this unwanted structural transformation. However, the true challenge probably originates from the continuous oxygen release upon charging. Here, the usage of dielectric polarization in surface coating to suppress the oxygen evolution of Li‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
108
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(111 citation statements)
references
References 83 publications
2
108
0
1
Order By: Relevance
“…In addition, the XPS spectra of NCM523 cathodes after 15 cycles ( Figure S17) revealed that triple-DMC/1,2-dfBen contributed to the formation of ac athode electrolyte interphase (CEI) layer containing -CF 3 and LiF. [30] Cycling tests were carried out by galvanostatically cycling the cells at 0.1 C(1C= 3mAcm À2 )for the first two cycles and then at 0.5 Cfor subsequent cycles ( Figure 5). Thecapacity of the cell with 1m LiPF 6 in EC/DEC decreased abruptly after only 17 cycles,which is attributed to the depletion of Li metal.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In addition, the XPS spectra of NCM523 cathodes after 15 cycles ( Figure S17) revealed that triple-DMC/1,2-dfBen contributed to the formation of ac athode electrolyte interphase (CEI) layer containing -CF 3 and LiF. [30] Cycling tests were carried out by galvanostatically cycling the cells at 0.1 C(1C= 3mAcm À2 )for the first two cycles and then at 0.5 Cfor subsequent cycles ( Figure 5). Thecapacity of the cell with 1m LiPF 6 in EC/DEC decreased abruptly after only 17 cycles,which is attributed to the depletion of Li metal.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…In addition to the spinel‐like surface, inverse spinel structure has also been reported recently. Chen's group [ 105 ] constructed a stable interphase of Mg 2 TiO 4 on the surface of commercial Li‐rich materials. The cell volume change caused by oxygen release for the modified material was reduced, as shown in Figure 7B.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…(B) In situ XRD results of fully charged LR and LR@MTO. Reproduced with permission from Ref [105]. Copyright 2020 WILEY‐VCH.…”
Section: Optimization Strategiesmentioning
confidence: 99%
“…Equally, use of LiAlBr 4 and LiAlI 4 with high voltage cathodes might be enabled with an appropriate coating of the positive electrode to prevent SSE decomposition. 37 , 38 Further investigations into various half- and full-cell architectures and their performance are currently underway and will be reported elsewhere.…”
mentioning
confidence: 99%